SINERGI PELAKSANAAN PENEGAKAN HUKUM LINGKUNGAN INDONESIA - Djafar, Eka Merdekawati (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2014)
Enforcement of environmental laws is expected to be carried out in synergy by law officers who are scattered in various law enforcement agencies in general and particularly in relation to environmental management. Understanding of the substance of environmental law should not be done partially adherence to environmental laws, both by the public and law enforcement officers itself so to create a legal substance is completely and thoroughly that understanding can be removed to the sectoral legislation. Likewise strongly support the creation of culture law enforcement of environmental law implementation synergies among law enforcement officers. It is intended that the law enforcement agencies have the same perception of the implementation of environmental law enforcement. Keyword : â€œ Law enforcementâ€ and â€œ Environmental Lawâ€